If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -8 = 2 + 3x Reorder the terms: -8 + 5x = 2 + 3x Solving -8 + 5x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -8 + 5x + -3x = 2 + 3x + -3x Combine like terms: 5x + -3x = 2x -8 + 2x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 -8 + 2x = 2 + 0 -8 + 2x = 2 Add '8' to each side of the equation. -8 + 8 + 2x = 2 + 8 Combine like terms: -8 + 8 = 0 0 + 2x = 2 + 8 2x = 2 + 8 Combine like terms: 2 + 8 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| 13(n-1)=5(2n+7) | | 6q+1=2q+6 | | 3d+4-9d+12= | | 3p+4.5=8 | | 2n+8=12 | | 3+3+x+x=22 | | x-3=2x+5 | | (x-8)(x-0.1)=0 | | 3(8-x)=2x | | 6(x-2)=3(x-2) | | 4x-9-3x=8x-1 | | 2(x-1)+3=x | | 3(x-1)=15 | | 5w-9=9-w | | 8=8-3h | | 1+7u=25 | | 7=3a+20 | | 20-2r=30 | | 7=9-3c | | 9(x-6)-2(x+5)=-2(x-6) | | -w+16=8 | | 8d-44=0 | | 13-9x=-14 | | 8d-44=9 | | 5d-12=3 | | 248-m=18 | | 2(x-1)+2(3-1)=5(x-9) | | 2x^2-6x+9=0 | | x+y+18=0 | | 6x^2-48x+30=0 | | 7y+19=15x | | 13x-6=2x+7+5x |